Agility in adversity: Vaccines on Demand. (1st September 2016) - De Groot, Anne S.; Moise, Leonard; Olive, David; Einck, Leo; Martin, William
ABSTRACT: Is the US ready for a biological attack using Ebola virus or Anthrax? Will vaccine developers be able to produce a Zika virus vaccine, before the epidemic spreads around the world? A recent report by The Blue Ribbon Study Panel on Biodefense argues that the US is not ready for these challenges, however, technologies and capabilities that could address these deficiencies are within reach . Vaccine technologies have advanced and readiness has improved in recent years, due to advances in sequencing technology and computational power making the 'vaccines on demand' concept a reality. Building a robust strategy to design effective biodefense vaccines from genome sequences harvested by real-time biosurveillance will benefit from technologies that are being brought to bear on the cancer cure 'moonshot'. When combined with flexible vaccine production platforms, vaccines on demand will relegate expensive and, in some cases, insufficiently effective vaccine stockpiles to the dust heap of history.